A decade of One Health implementation in Somalia: Challenges and opportunities for institutionalization - Hared, Y.A.; Mumin, F.I.; Mor, Siobhan M.; Mohamed, S.A.; Nguka, G.; Knight-Jones, Theodore J.D.; Richards, Shauna (CAB International, 2025)
One Health (OH)-oriented initiatives are essential for addressing complex health challenges in Somalia given the country’s economy depends heavily on the livestock, agriculture, and marine resources. The Capacitating One Health in Eastern and Southern Africa (COHESA) project supported a comprehensive assessment of the status of OH in Somalia through 21 key informant interviews, two focus group discussions, a desk review of secondary data and net-mapping with OH stakeholders. This multi-faceted approach aimed to deepen the understanding of OH concepts and their interconnectedness with human, animal, and ecosystem health. The study identified several critical challenges and opportunities within the Somali context, focusing on innovations in governance, education, and implementation. Key findings revealed significant gaps, including limited infrastructure, insufficient government funding for OH initiatives, and an overreliance on external donor support. Moreover, there is a notable lack of institutionalization of OH within various government sectors, which hinders effective collaboration. This assessment underscores the urgent need for enhanced funding, capacity building, and the establishment of sustainable governance structures. By addressing these gaps, Somalia can leverage OH principles to improve health outcomes for humans, animals, and the environment, thereby fostering a healthier and more resilient society.